2021
DOI: 10.3389/fmats.2021.666202
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Derived Nanobiomaterials as a Potential Next Generation Dental Implant Surface Modifier

Abstract: Dental implants resemble synthetic materials, mainly designed as teeth-mimics to replace the damaged or irregular teeth. Specifically, they are demarcated as a surgical fixture of artificial implant materials, which are placed into the jawbone, and are allowed to be fused with the bone, similar to natural teeth. Dental implants may be categorized into endosteal, subperiosteal, and zygomatic classes, based on the placement of the implant “in the bone” or on top of the jawbone, under the gum tissue. In general, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…In addition to the advantages of metal and ceramic-based dental implants, several limitations like toxicities and corrosive behavior are also associated with them. To overcome these challenges, less toxic plant-derived biomaterials are used in the production of dental implants [ 139 ]. A recent study reported that gold NPs were photo-fabricated from aqueous bark extract of Salacia chinensis and applied in dental implants, where it was shown its biocompatibility with blood and high osseoinductive potential when evaluating the cell viability with MG-63 bone osteosarcoma cell lines [ 140 ].…”
Section: Application Of the Nano Dentistrymentioning
confidence: 99%
“…In addition to the advantages of metal and ceramic-based dental implants, several limitations like toxicities and corrosive behavior are also associated with them. To overcome these challenges, less toxic plant-derived biomaterials are used in the production of dental implants [ 139 ]. A recent study reported that gold NPs were photo-fabricated from aqueous bark extract of Salacia chinensis and applied in dental implants, where it was shown its biocompatibility with blood and high osseoinductive potential when evaluating the cell viability with MG-63 bone osteosarcoma cell lines [ 140 ].…”
Section: Application Of the Nano Dentistrymentioning
confidence: 99%
“…Silver nanoparticles produced with Oleo europaea extract (white pepper oleoresin) showed increased antibacterial activity against oral infections. Because of their ability to inhibit microbial growth, they can be useful as a surface modification for traditional dental implants [ 155 , 156 , 157 ].…”
Section: Applications Of Ag-np'sin Dental Implantmentioning
confidence: 99%
“…All of thisresearch showed that Nano biomaterials have great potential for use in dental implants.Potentially, innovative Phyto Nano biomaterials for dental implants might be more easily manufactured as a result of developments in contemporary synthesis procedures [ 155 , 156 , 157 ]. Applications of AgNPs in dental implants can be seen in Figure 10 .…”
Section: Applications Of Ag-np'sin Dental Implantmentioning
confidence: 99%
See 1 more Smart Citation
“…The widespread applications of nanomaterials in biomedical sciences embody one of the paramount advancements in research targeting the utilization of submicroscopic particles. Evidently, this transcends numerous diverse domains, such as the mode of synthesis, mechanisms of vesicular carrier formation, risks and toxicity assessment, diagnostic and healing potential, source or origin of raw materials, characteristic size and charge range, among others (Jeevanandam et al, 2017;Nnaji et al, 2018;Tan et al, 2018;Tan et al, 2019;Fytianos et al, 2020;Has and Pan, 2020;Tan et al, 2020;Pan et al, 2021a;Jeevanandam et al, 2021). To highlight the perspective, one may consider the recent developments in the enhanced utilization of gold-based nanomaterials in several capacities towards generating antimicrobial actions in general, and antibacterial effects, in particular (Mutalik et al, 2020;Yougbaré et al, 2021).…”
Section: Introductionmentioning
confidence: 99%